Statistical Model Applied to NetFlow for Network Intrusion Detection - Proto, Andre [UNESP]; Alexandre, Leandro A.; Batista, Maira L.; Oliveira, Isabela L.; Cansian, Adriano M.; Gavrilova, M. L.; Tan, CJK; Moreno, E. D. (Springer, 2010)
The computers and network services became presence guaranteed in several places. These characteristics resulted in the growth of illicit events and therefore the computers and networks security has become an essential point in any computing environment. Many methodologies were created to identify these events; however, with increasing of users and services on the Internet, many difficulties are found in trying to monitor a large network environment. This paper proposes a methodology for events detection in large-scale networks. The proposal approaches the anomaly detection using the NetFlow protocol, statistical methods and monitoring the environment in a best time for the application.
Keywords: Security; network; statistical; NetFlow; intrusion detection; anomaly